Balancing Sovereignty and Protection: Rekonsiliasi Kebijakan Control Host State tentang Hilirisasi Sumber Daya Alam Dengan Pengutamaan Prinsip Fair and Equitable Treatment (FET) - Thareq Hafiz Hidayat (Universitas Insan Budi Utomo, 2026)
The natural resource downstreaming policy implemented by the Government of Indonesia through restrictions on raw material exports and domestic processing requirements is a clear manifestation of the Host State Control doctrine and the state's inherent right to regulate its natural wealth. However, within the realm of international investment law, the implementation of such restrictive policies often clashes sharply with the absolute standard of treatment for foreign investors, specifically the Fair and Equitable Treatment (FET) clause. This paper analyzes the compatibility of the downstreaming policy with the FET principle and formulates reconciliatory measures that the government must undertake to mitigate the risk of lawsuits in international arbitration forums (ISDS). Conceptually, the downstreaming policy is deemed consistent with and does not violate the FET principle, provided that its application is conducted in good faith (bona fide), non-discriminatory, and based on legitimate public policy goals for national economic development. Based on international jurisprudence, the FET principle does not guarantee an absolute static regulatory environment (frozen regulatory framework) unless specific written assurances are breached. Nevertheless, the potential for FET violations remains wide open at the technical implementation level if the government acts inconsistently, lacks transparency, or violates the proportionality principle, which could destroy the commercial value of the investor's initial investment. To reconcile state sovereignty and investor protection, the Government of Indonesia needs to adopt strategic reconciliatory measures. These steps include providing an adequate grace period (grandfathering clause), maintaining regulatory consistency across institutions, offering accommodative fiscal and non-fiscal incentives, strengthening multi-tiered dispute resolution mechanisms (cooling-off periods), and reforming the architecture of international investment agreements through new-generation Bilateral Investment Treaties (BITs) that narrow the scope of the FET clause. Through this